Basal Body Temperature Difference Before and During The Endometrial Wall Decay on The Menstrual Cycle - Ika Mustika; Nova Lusiana; Estri Kusumawati; Risa Purnamasari (State Islamic University of Sunan Ampel, 2018)
The menstrual cycle is a complex process involving hormones and reproductive organs. Hormonal changes that occur in the menstrual cycle result in changes in body basal temperature in women. Basal body temperatures can identify phase changes in one menstrual cycle. This study is to determine whether there is influence of decay of the endometrium wall against the basal body temperature in adolescent girls. This research is observational analytic with cross sectional time approach. This study was conducted on 60 samples with the age of 19-22 years. Data used in this research are primary data that is basal body temperature measurement and questioner. The analysis in this study is paired sample t test test using SPSS 16. The results obtained significance value of 0.003 <0.05, so it can be concluded that there is influence of decay of the endometrium wall in the menstrual cycle against changes in basal body temperature. The endometrial wall decay on the menstrual cycle causes basal body temperature decreased compare with before the uterine lining decay or menstruation.